2015
DOI: 10.1120/jacmp.v16i2.5204
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative comparison of automatic and manual IMRT optimization for prostate cancer: the benefits of DVH prediction

Abstract: A recent publication indicated that the patient anatomical feature (PAF) model was capable of predicting optimal objectives based on past experience. In this study, the benefits of IMRT optimization using PAF‐predicted objectives as guidance for prostate were evaluated. Three different optimization methods were compared. 1) Expert Plan: Ten prostate cases (16 plans) were planned by an expert planner using conventional trial‐and‐error approach started with institutional modified OAR and PTV constraints. Optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
(21 reference statements)
1
10
0
Order By: Relevance
“…This study had several limitations. Planning time was not explicitly recorded in this research since KBP has been extensively shown to improve planning efficiency . However, average KBP planning time was qualitatively comparable to average reference planning time in the present study.…”
Section: Discussionsupporting
confidence: 54%
“…This study had several limitations. Planning time was not explicitly recorded in this research since KBP has been extensively shown to improve planning efficiency . However, average KBP planning time was qualitatively comparable to average reference planning time in the present study.…”
Section: Discussionsupporting
confidence: 54%
“…The predicted DVH curves from both models were used to extract the dose-volume objectives for both the bladder and rectum to guide treatment planning. 30 As shown in Fig. 6, the prediction from the outlier-added model was less favorable than that of the outlier-free-model which agreed better with the clinical plan DVH.…”
Section: Discussionmentioning
confidence: 77%
“…A prostate model without a dosimetric outlier and a prostate model with 10 dosimetric outliers were tested on a fresh prostate case that was not used to train the models. The predicted DVH curves from both models were used to extract the dose‐volume objectives for both the bladder and rectum to guide treatment planning . As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…79 To gain further understanding of the overall performance of KBP in prostate cancer planning, we have developed a visualization scheme to provide a summary view of nine KBP prostate studies that compared re-planned results with original clinically approved values. 20,25,27,34,35,56,57,60,63 As mentioned previously, the challenge of summarizing results across all studies lie in two aspects: (a) the results are based on different sample points of the DVH curve and measure changes along different directions (e.g., one study may use D35 while another use V65); (b) some of the studies report only the differences in DVH point metrics (e.g., D35 is reduced by 1.5) without providing the original clinically approved values. The first issue makes it difficult to quantitatively compare results from different studies even though many DVH point metrics assess performance in similar areas of the DVH curve.…”
Section: C Performance Of Kbpmentioning
confidence: 99%
“…And some studies suggest that this is true especially for models learned from experienced planners' datasets and applied to cases generated by either inexperienced planners or planners who are not experienced with a planning system. Some studies 15,20,22,28,31 have also compared the time and efficiency of KBP methods to the current manual planning process. In all cases, the KBP methods were faster and the improvement is more significant for more complex cases.…”
Section: C Performance Of Kbpmentioning
confidence: 99%